2023
DOI: 10.7759/cureus.38211
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Oxycodone and Hydrocodone Distribution Trends in Delaware, Maryland, and Virginia Between 2006 and 2014

Abstract: Objective Opioid medications are widely recognized for their use in analgesia and their addictive properties that have led to the opioid epidemic. Areas with historically high prescribing patterns have been shown to suffer more from the crisis. There is also regional variability in these trends. This study is a county level analysis of oxycodone and hydrocodone use in Delaware, Maryland, and Virginia between 2006 and 2014. Materials and methods A retrospective analysis of oxyco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 18 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…Interestingly, Florida’s decline in opioid distribution after 2010 was not unique. Eufemio et al found the same timing of decline in Delaware, Maryland, and Virginia [ 30 ]. Although the authors believed this decline in oxycodone and hydrocodone to be due to stricter regulation as well, these three states implemented PDMPs at scattered points in time (Delaware in 2012, Maryland in 2018, Virginia in 2003) without much temporal correlation with the decline in opioids [ 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Interestingly, Florida’s decline in opioid distribution after 2010 was not unique. Eufemio et al found the same timing of decline in Delaware, Maryland, and Virginia [ 30 ]. Although the authors believed this decline in oxycodone and hydrocodone to be due to stricter regulation as well, these three states implemented PDMPs at scattered points in time (Delaware in 2012, Maryland in 2018, Virginia in 2003) without much temporal correlation with the decline in opioids [ 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 93%
“…The anticipation of hydrocodone rescheduling may have contributed to providers choosing other less scrutinized pain relievers, like the previously uncontrolled, unscheduled tramadol [ 52 ]. This explanation is limited, however, as analyses in other states (Delaware, Maryland, and Viriginia) found that hydrocodone did increase from 2006 to 2010, although not as dramatically as oxycodone [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were stark differences in the patterns of change between states. Some, like Florida 16 or Delaware, 15 increased substantially leading up to 2010 and dropped off just as quickly. Others like Texas 14 or Illinois maintained consistently low distribution, and many states fell somewhere in between.…”
Section: Discussionmentioning
confidence: 99%
“…13 Here, we explore oxycodone distribution by state using the US Drug Enforcement Agency (DEA) ARCOS over a larger time frame than any previous studies, which included reports on prescription opioids in the US territories, Texas and throughout Delaware, Maryland and Virginia. [14][15][16] Past works frequently rely on the IQVIA database, which is limited by gaps in oxycodone, including data from Veteran's Affairs, Indian Health Services facilities, hospitals and independent pharmacies. 17 Using states as the geographical unit allows results to be interpreted in the context of laws and regulations which apply at that level.…”
Section: Open Accessmentioning
confidence: 99%